A Comparitive Analysis of EAP Authentication Mechanism for WLAN - Singare, Yogesh; Tembhurkar, Manish (International Journal of Computer Sciences and Engineering, 2015)
In recent years, WLANs have been developing rapidly and are increasingly being used in many applications. The extensive application of WLAN has been using an authentication framework widely called as Extensible Authentication Protocol (EAP). The requirements for EAP methods (i.e. Authentication mechanisms built on EAP) in WLAN authentication have been defined in RFC 4017 are issues also increasingly receiving widespread attention. To achieve user efficiency and robust security, lightweight computation and forward secrecy, not included in RFC 4017, are also desired in WLAN authentication. However, all EAP methods and authentication protocols designed for WLANs so far do not satisfy all of the above properties. With detailed analysis of all EAP Methods and authentication protocols designed for WLANs, this article pointed out properties of all EAP method.